Relationship Between Depressive Symptoms and Quality of Life in Family Caregivers of Dependent Children: A Systematic Review with Meta-Analysis - Francisco Segura-Galán; Catalina López-Martínez; Belen Gutiérrez-Sánchez; Rafael del-Pino-Casado (Healthcare, 2026)
Background: Caring for dependent children with chronic illnesses or disabilities constitutes a major public health challenge, subjecting family caregivers to prolonged physical and emotional stressors. Objectives: To quantitatively synthesize the relationship between depressive symptomatology and quality of life (QoL) in this population. Methods: A systematic review methodology with meta-analysis was conducted following PRISMA guidelines and Cochrane handbook recommendations. Databases such as PubMed, CINAHL, PsycInfo and Scopus were consulted up to February 2026. Results: Thirty-three original studies evaluating family caregivers of children under 18 years of age and reporting statistical data of association were included. The meta-analysis revealed a statistically significant moderate-to-strong negative association between depressive symptoms and overall QoL (r = −0.532; I2 = 9.51%), maintaining similar values across all analyzed domains (physical, mental, social and environmental) as well as the summary components of the SF-36 questionnaire. According to the GRADE criteria, the overall certainty of evidence was rated as low to very low across all QoL domains and SF-36 components. Conclusions: This study demonstrates that heightened depressive symptomatology is substantially associated with compromised well-being among family caregivers.